La0.4Sr0.6Co0.7Fe0.2Nb0.1O3-δ perovskite prepared by the sol-gel method with superior performance as a bifunctional oxygen electrocatalyst. (6th November 2020) - Yu, Longjiao; Xu, Na; Zhu, Tenglong; Xu, Zhanlin; Sun, Mengzhen; Geng, Duo
Abstract: The advancement of efficient noble-metal-free electrocatalysts for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) is crucially important for energy storage devices such as fuel cells and metal-air batteries. This paper reports the development of a novel bifunctional perovskite, La0.4 Sr0.6 Co0.7 Fe0.2 Nb0.1 O3-δ (LSCFN). The crystal structure, morphology, adsorption, valence, and oxygen catalytic activity of LSCFN were systematically studied. In addition, an investigation of the influence of the synthetic method on the oxygen catalytic activity was performed. Sol-gel and solid-phase methods were applied for the synthesis of LSCFN, and the resulting perovskites were denoted as LSCFN-SG and LSCFN-SP, respectively. The catalyst LSCFN-SG exhibited excellent bifunctional catalytic activity, with a low overpotential (360 mV) and superior stability in the OER. Subsequently, LSCFN-SG was used as the cathode catalyst in an aluminum-air battery and exhibited a high power density. The results of this study indicate that LSCFN-SG is a promising bifunctional oxygen electrocatalyst for metal-air batteries. Highlights: LSFCN-SG exhibits superior bifunctional catalytic activity. LSCFN-SG catalyst successfully facilitates the performance of aluminum-air batteries. O species and the oxidation state of the B-site cations enhanced the activity.